Marketing Mix Analysis In Improving Decisions To Purchase Yamaha Brand Motorcycles In Kotabumi Tangerang - Sugandha; Rinintha Parameswari; Suhendar Janamarta; Fidellis Wato Tholok (LPPM Universitas Buddhi Dharma, 2024)
In conducting this research, data collection techniques were used and in distributing it in the form of a questionnaire, in this research the calculated product t value was 2.953 which is greater than the t table of 1.661 and the probability of 0.004 is smaller < 0.05, the calculated t value of promotion 2.489 is greater than the t table of 1.661 and the probability of 0.015 is smaller < 0.05, the t calculated price value of 5.763 is greater than the t table of 1.661 and the probability of 0.000 is smaller < 0.05 , the t calculated place value of 6.683 is greater than the t table of 1.661 and the probability of 0.000 is smaller < 0.05.